2022
DOI: 10.2147/cia.s354519
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Correction of Low Hemoglobin Levels Can Reduce 1-Year All-Cause Mortality in Osteoporotic Hip Fracture Patients: A Retrospective Observational Study

Abstract: Purpose Osteoporotic hip fracture surgery is associated with a risk of morbidity and mortality. Admission hemoglobin levels <10 g/dL have been documented as a strong predictor of mortality risk. This study aimed to investigate the mortality outcome between osteoporotic hip fracture patients who had preoperative hemoglobin levels raised to ≥10 g/dL and those with hemoglobin levels were <10 g/dL. Patients and Methods This 5-year retrospective observational study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
5
6
0
Order By: Relevance
“…Some studies have reported some of management measures can reduce 1-year all-cause mortality in hip fracture patients. Our studies also have similar results [ 25 ]. From the results, we learned that the integrated management bundle made a significant survival benefit on the survival curve of super elderly hip fracture patients.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Some studies have reported some of management measures can reduce 1-year all-cause mortality in hip fracture patients. Our studies also have similar results [ 25 ]. From the results, we learned that the integrated management bundle made a significant survival benefit on the survival curve of super elderly hip fracture patients.…”
Section: Discussionsupporting
confidence: 88%
“…Blood management measures include correction of preoperative low hemoglobin levels. Worapaka Manosroi et.al reported preoperative correction of low hemoglobin levels can reduce 1-year all-cause mortality in hip fracture patients [ 25 ]. They believed that this was related to an increase of the oxygen-carrying capacity of blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal analysis in old adults without anemia showed that higher hemoglobin levels were linked with better physical performance 16 . One observational study found that in patients with hip fracture, preoperative hemoglobin levels ≥ 10 g/dl lead to a 50% decreased risk of mortality compared to patients with hemoglobin levels < 10 g/dl (hazard ration(HR) = 0.50, 95% CI 0.25–0.99, P = 0.048) 17 . Another research investigated the outcomes in patients with chronic kidney disease under cardiac surgery and indicated that with 1 g/dl decrement in hemoglobin, the values of OR in mortality, sepsis, cerebrovascular complication and postoperative hemodialysis were 1.38(95%CI 1.23–1.57; P = 0.001), 1.31 (95%CI 1.14–1.49; P = 0.001), 1.31 (95%CI 1.00–1.67; P = 0.030), and 1.38 (95%CI 1.11–1.75; P = 0.010), respectively 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Ascertaining the precise amount of hemoglobin loss during hospitalization poses a challenge. Consequently, it is not possible to directly assess the relationship between postoperative hemoglobin levels and the likelihood of death 17 . In contrast to previous research suggesting that the hemoglobin (Hb) level at admission is a signi cant independent predictor of postoperative mortality in elderly patients with hip fracture 18 , our study used Delta hemoglobin to evaluate the amount of hemoglobin loss during hospitalization.…”
Section: Discussionmentioning
confidence: 99%